The Shrinking German Middle Class: Signs of Long-Term Polarization in Disposable Income? - Markus M. Grabka; Joachim R. Frick (Weekly Report, 2008)
The proportion of middle income earners in Germany has shrunk significantly in recent years: from 62 percent of the total population in the year 2000 to only 54 percent in 2006. Correspondingly, the proportion of the population at the margins of the income distribution has increased as well, while the downward mobility among the middle class was more marked than the upward mobility in higher income strata. In line with the changes in the objective income situation, significant changes have also been seen in subjective perceptions: across all income strata, we find that people's concerns about their personal economic situation have increased.
Keywords: D31; I32; 330; Income Inequality; Middle Class; Poverty